Use of 3D-DXA in the assessment of bone structure among patients with chronic kidney disease - Martin Kužma; Zuzana Kužmová; Ludovic Humbert; Mirella Lopez Picazo; Roman Králik; Jakub Falat; Juraj Smaha; Peter Jackuliak; Zdenko Killinger; Juraj Payer (Frontiers in Medicine)
IntroductionPatients in later stages of chronic kidney disease (CKD) have a 2- to 14-fold increase in fracture risk. Bone mineral density (BMD) assessment is limited due to the inability to measure trabecular and cortical bone characteristics and the interference of aortic calcifications.Study objectiveThis study aimed to assess the trabecular bone score (TBS) and three-dimensional dual-energy X-ray absorptiometry (3D-DXA) in participants across all CKD stages.Patients and methodsIn total, 64 CKD patients (consisting of 28 female participants and 36 male participants, with an average age of 69.5 years) were included. There were 9, 12, 8, 9, 11, and 15 participants in stages G1, G2, G3a, G3b, G4, and G5 of CKD, respectively. BMD at the lumbar spine (LS) and proximal femur, as well as the LS TBS, were analyzed. The proximal femur parameters such as cortical and trabecular volumetric (v)BMD, cortical thickness (CTh), and surface (s)BMD at the total hip (TH) and femoral neck (FN) were analyzed using 3D-Shaper software.ResultsComparison between the earlier stages (G1-G3a) and the later CKD stages (G3b-G5) showed significant differences in carboxy terminal collagen crosslinks (CTx) (386 vs.1053 ng/L), TH areal bone mineral density (aBMD; 0.991 vs. 0.859 g/cm2), cortical TH vBMD (831 vs. 795 mg/cm3), FN (837 vs. 788 mg/cm3), TH cortical sBMD (170 mg/cm2), and TH Cth (2.03 vs. 1.92 mm; all p < 0.05). Cross-sectional comparisons between each CKD stage showed a gradual decrease in the LS BMD, TH cortical vBMD, sBMD (FN and TH), and TH Cth. Strong positive associations between the glomerular filtration rate (GFR) and cortical parameters (FN/TH vBMD and TH Cth) were observed (p < 0.01).ConclusionIn conclusion, advanced stages of CKD (G3b–G5) were associated with lower cortical bone parameters. The majority of the cortical parameters were correlated with the GFR, demonstrating a direct relationship between the kidney function and bone structure.